Analysis of PM2.5 pollution episodes in Beijing from 2014 to 2017: Classification, interannual variations and associations with meteorological features. (15th September 2019) - Sun, Jin; Gong, Jianhua; Zhou, Jieping; Liu, Jiantao; Liang, Jianming
Abstract: Ambient PM2.5 pollution has been a major environmental concern in recent years. Beijing, the capital of China, is enduring frequent and severe PM2.5 pollution. In this study, 186 valid PM2.5 pollution episodes during the 2014-2017 period were identified and classified into four categories according to the mechanism of pollution formation and evolution. Category I often occurs in autumn, winter and early spring, depending on accumulation during stagnant weather. Category II featured by photochemistry is dominant in summer, and category III caused by dust storms occasionally occurs in spring. Category IV represents a combination during transition periods. Interannual variations show that particulate pollution decreased from 2014 to 2017, and the decline in categories I and II played the most important role. To further understand the PM2.5 pollution patterns in Beijing, the temporal and spatial characteristics and relationships between PM2.5 levels and meteorological features were analyzed. Category I is the main pollution type that brings forth heavy or severe pollution and has the longest duration in those cases, while category II often leads to light or moderate pollution. There is a north-south gap in the PM2.5 levels in Beijing. The high-level pollution in category I tends to evolve northward, while the low-level pollution in category I and category II pollution tend to evolve southward and widen the north-south gap, affected by the regional transport and more local emissions in the south. Additionally, the relationship between the concentrations and meteorology also vary with the pollution categories. High relative humidity, low wind speeds and low boundary layer heights are likely to lead to category I or II pollution, but category III requires high winds. These results provide insights into the annual tendency and characteristics of Beijing's particulate pollution in recent years. Graphical abstract: Image 1 Highlights: The PM2.5 pollution episodes from 2014 to 2017 were identified and classified. Particle pollution has been decreasing in recent years due to the decline in accumulation and photochemistry types. Most of the heavy and severe pollution is due to the type of accumulation. There is a north-south gap in PM2.5 levels in Beijing. The relationships between PM2.5 levels and meteorological features vary with pollution categories.